Developing Students’ Responsibility and Scientific Creativity through Creative Responsibility Based Learning in Learning Physics - Muhammad Feyzar Rif 'at; Mustika Wati; Suyidno Suyidno (Berkala Ilmiah Pendidikan Fisika, 2020)
Development of scientific responsibility and creativity in learning physics are included in the key competencies in the industrial era 4.0. However, both of these competencies are not used in school. Therefore, the purpose of this study is to analyze the effectiveness of Creative Responsibility Based Learning in developing students' responsibility and scientific creativity. This research is part of the research and development of the ADDIE model. Trial implementation using one group pre-test and post-test design on 27 students of Class XI-2 MAN 2 Banjarmasin. Data collection instruments consist of responsibility observation and scientific creativity tests. After being CRBL implemented, the students’ responsibility increased at each meeting in good criteria. Also, the value of n-gain scientific creativity by 0.34 in moderate criteria. Thus, CRBL is effective in developing the students’ responsibility and scientific creativity in learning physics.